Adverse childhood experiences and adolescent drug use in the UK: The moderating role of socioeconomic position and ethnicity. (September 2022) - Karamanos, A.; Stewart, K.; Harding, S.; Kelly, Y.; Lacey, R.E.
Abstract: Rationale: There is a paucity of prospective UK studies exploring the role of Adverse Childhood Experiences (ACEs) on adolescent teenage drug use and even less is known about the complex interplay between ACEs and adolescent social, demographic, and economic characteristics. To address these gaps, we use rich longitudinal data from the nationally representative Millennium Cohort Study. Methods: Sex-stratified survey logistic regression modelling was applied using data from 9, 476 adolescents and their parents to examine associations between ACEs between ages 3 and 14 years and drug use at ages 14 and 17 years. We a) explore the extent to which associations are robust to adjustment for ethnicity, family income, parental social class, and parental education, b) examine whether associations differ by these factors, and c) estimate the proportion of drug use at ages 14 and 17 years attributable to ACEs after controlling for these factors. Results: Half of MCS cohort members had been exposed to at least one ACE and approximately 1 in 11 were exposed to 3+ ACEs. Multivariable analyses suggest that ACEs were associated with a higher likelihood of drug use at age 14 than age 17, especially for girls. No evidence was found that either advantaged socio-economic position or ethnicity acted as a buffer against the negative effects of ACEs in relation to adolescent drug use. Finally, we found that prevention of exposure to sexual violence, bullying and violence within the household (if causal) is more important for girls' drug use at age 14 than age 17. Conclusions: ACEs are associated with adolescent drug use with potential consequences on wider aspects of young people's lives, regardless of their social, ethnic, or economic background, adding further urgency to the need to reduce the incidence of these negative experiences. Highlights: PAFs for drug use at age 14 were higher compared to age 17. ACEs-drug use associations were stronger for girls than boys.